Um estudo das geometrias prática e teórica presentes em The Pathewaie to Knowledge de Robert Recorde: possíveis diálogos - Bento, Regina Thaíse Ferreira (2018)
In this work we present the English mathematician Robert Record (1512-1558) and his treatise on geometry titled The Pathewaie to Knowledge, written in modern English and whose first edition was printed in the year 1551. We analyze in this treatise the presence and possible dialogue established between the geometric knowledge from ancient traditions linked to practice and the theoretical geometry that is studied in the universities and is based on the geometric treatise written by Euclides. To do so, we analyze the context in which the work and its author were inserted, identify what mathematical knowledge is present in this treatise and how they relate to the mathematical practices and the scholarly knowledge of the time. In addition, we sought indications that would allow us to evidence the presence of other geometric. This analysis was made use of the articulation between three spheres: the historiographical, the contextual and the epistemological. This combination gave us a broader look at the possible motivations that would have led Recorde to write the treatise in question. We find that Record was a man cultivated and attentive to the demands of his people and his time. Sixteenth-century England was at a time of social, political, and religious transformation; there was a great demand for investments in the practical-oriented sciences such as artillery, horology, navigation, and land measurement. Thus, professionals such as land surveyors and navigators assumed a determining role for the development of England and needed greater mathematical knowledge to advance their practices. However, access to education was restricted to most of the population and the little available material was written in Latin. This demand for mathematical knowledge practiced in this period, such as arithmetic, algebra, and geometry, made professionals who mastered their craft begin to produce materials written in the vernacular. Recorde, with his privileged background, was the first to produce a collection of textbooks in English with basic mathematics aimed directly at the interests of these professionals. The Pathewaie to Knowledge was the first treatise on practical geometry written in English. At that time practical and theoretical geometry were independent. With the results of this work it is concluded that in fact Robert Record established a dialogue between practical and theoretical geometries, contributing to the dissemination of speculative mathematical knowledge and the validation of geometry used for centuries by mathematicians. This analysis indicates that the understanding of the process that involves the construction of mathematical knowledge can effectively aid in a more critical learning by mathematical educators